The Effect of Implementing Mind Mapping in Group Guidance on Students’ Career Planning - Muh. Dadang (Program Studi bimbingan Konseling PPs UNM Makassar, 2021)
This study aims to (i) describe the career planning of the 8th grade students of SMPN 9 Bulukumba before and after being given the mind mapping method in group guidance; (ii) describe the mind mapping technique used in guidance group for career planning of the 8th grade students of SMPN 9 Bulukumba; and (iii) investigate the effect of mind mapping used in guidance group on the career planning of the students of SMPN 9 Bulukumba. This study employed a quantitative approach with a quasi-experimental design focusing on nonequivalent control group design. The data were collected using career planning scale and analyzed using the statistic independent samples t-test. The results of the study showed (i) career planning among the 8th grade students of SMPN 9 Bulukumba was low before mind mapping was given in group guidance, but after mind mapping was implemented in group guidance, the significance of the change was considered high and (ii) mind mapping in group guidance affects career planning among the 8th grade students of SMPN 9 Bulukumba.